An empirical model for predicting voluntary intake of forage-legume-supplemented roughages by cattle - Nsahlai, I.V.; Umunna, N.N.; Osuji, P.O. (South African Society of Animal Science, 1996)
Where VRI is a function of basal roughage quality (nitrogen and fibre (NDF) contents, rumen dry matter degradability), CF basal is the correction factor for other attributes of the roughage (cropping and processing methods and forms of offer), CF sup is the correction factor for supplement attributes (quantity. quality and interaction of roughage quality with supplementation). CF animal is the correction factor for animal attributes (live weight, sex and breed), CF envir is the correction factor for environmental attributes (temperature and period of undermourishment). Hereunder are some salient effects captured in the model: Urea-treatment increased VRI by 13 percent. Forages comprising of legume-straw mixtures induced varied intakes between breeds attributable to their quality and to whether or not it is a whole crop. Heifers consumed 10 percent less than steers, but response due to supplementation was higher in heifers than in steers. Crossbred calves consumed 20 percent more roughage than Zebus, but responses to supplementation where similar in both breeds. VRI decreased exponentially with increasing live weight. The rate of decrease was a function of roughage quality and is slower for good quality ones. VRI decreased with increasing daily maximum temperature but increased with increasing period of undernourishment. The model for VRI accounted for 73 to 79 percent of the variation in voluntary intake. To widen the application of the model cross regional calibration is suggested and the effects of physiological status (pregnancy and lactation) and work strees are being investigated.